Active Disturbance Rejection Control for Unmanned Aerial Vehicle - Marwan, Hakam; Humaidi, Amjad J.; Al-Khazraji, Huthaifa (International Journal of Robotics and Control Systems, 2025)
This paper presents the design and analysis of a roll motion control system for a vertical take-off and landing of unmanned aerial car (VTOL-UAV) during the hovering flight phase. Ensuring stability and disturbance rejection during hovering is a significant challenge for UAVs, as external disturbances can lead to instability. To address these challenges, this study proposes an Active Disturbance Rejection Control (ADRC) strategy to enhance the system's roll stability and disturbance rejection. The primary contribution is the development of an improved ADRC system by integrating different types of extended state observers (ESO) with a Nonlinear-Proportional-Derivative (NPD) controller. The paper evaluates three ESO types—Linear (LESO), Nonlinear (NESO), and Fractional Order (FOESO)—for system state estimation and disturbance compensation. By combining the best ESO with NPD controller, an enhanced ADRC system is formed and its performance is compared against a conventional Proportional-Integral-Derivative (PID) controller. Numerical simulations performed using MATLAB demonstrate that ADRC significantly improves roll stability and disturbance rejection under both disturbed and undisturbed conditions. The results indicate that the LESO provides the best estimation accuracy, leading to superior system robustness. The ADRC system with LESO outperforms the PID controller in all test cases, particularly in disturbance rejection and stability. The study concludes that ADRC with LESO is an effective solution for improving VTOL-UAV roll motion control during hovering providing a promising approach for future UAV applications in dynamic environments.